2021
DOI: 10.1042/cs20210858
|View full text |Cite
|
Sign up to set email alerts
|

Early elimination of uremic toxin ameliorates AKI-to-CKD transition

Abstract: Acute kidney injury (AKI)-related fibrosis is a major driver of chronic kidney disease (CKD) development. Aberrant kidney recovery after AKI is multifactorial and still unclear. The accumulation of indoxyl sulfate (IS), a protein-bound uremic toxin, has been identified as a detrimental factor of renal fibrosis. However, the mechanisms underlying IS-related aberrant kidney recovery after AKI is still unknown. The study aims to elucidate the effects of IS in the pathogenesis of AKI to CKD transition. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…It has been found that IS accumulates in an in vivo AKI model [29,31]. Different to BUN and sCr levels which return to normal levels in the recovery stage of AKI [25], furthermore, our current work found that accumulation of the secreted PBUT is sustained without an increase in BUN and sCr after 10 days of unilateral ischemia-reperfusion injury mice model [32]. Therefore, we thought UIRI model would be a suitable model to investigate the roles of PBUTs in AKI to CKD transition.…”
Section: Loss Of Secretory Function In Renal Tubular Epithelial Cells After Akisupporting
confidence: 52%
See 2 more Smart Citations
“…It has been found that IS accumulates in an in vivo AKI model [29,31]. Different to BUN and sCr levels which return to normal levels in the recovery stage of AKI [25], furthermore, our current work found that accumulation of the secreted PBUT is sustained without an increase in BUN and sCr after 10 days of unilateral ischemia-reperfusion injury mice model [32]. Therefore, we thought UIRI model would be a suitable model to investigate the roles of PBUTs in AKI to CKD transition.…”
Section: Loss Of Secretory Function In Renal Tubular Epithelial Cells After Akisupporting
confidence: 52%
“…During exposure to PBUTs, fibroblasts are directly activated by IS or PCS stimulation or indirectly by tubular secreted TGF-β then leading to myofibroblast activation and extracellular matrix deposition [52][53][54]. Chen et al indicated that oral gavage of the IS precursor-indole accelerated AKI to CKD progression in an ER stress-dependent manner [32]. Furthermore, several studies support the concept that AKI insults promote premature aging development [55,56].…”
Section: Potential Mechanism Of Uremic Toxin Retention Involved In Aki To Ckd Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell growth and proliferation ability were measured with CellTiter 96 ® Aqueous One Solution Cell Proliferation kit (Promega). The detailed procedure was described as previous [ 30 ]. Briefly, HK-2 cells were plated in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…However, the association between IS, cardiovascular dysfunction, and cardiovascular complications can also be explained by the pathological action of IS on kidney disease progression. Indeed, several experimental studies have highlighted the effect of IS on the development of renal fibrosis through oxidative stress, the activation of endoplasmic reticulum stress, and the epithelial-mesenchymal transition [ 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Gut-derived Protein-bound Uremic Toxins and Cardiovascular D...mentioning
confidence: 99%